Power quality improvement of a PV and fuel cell connected microgrid - P, Saisrinivas; Kalavathi. M, Surya; V, Varunrohit (International Journal of Engineering and Technology, 2018)
Increasing demands of 21st century gain the need for sustainable energy. Non-conventional energy sources like solar, wind, fuel cell etc. are attaining much importance because of increasing environmental issues like Global Warming, Increase in Carbon foot prints etc. But, Non-conventional energy sources are not controllable. Hence, there is a need of sophisticated control of energies available to use them collectively. This can be made possible by the concept of Microgrid.This paper presents the work done on a typical grid connected Microgrid, with Solar and Fuel cell as non-conventional energy sources, using MATLAB (Simulink). A variable irradiance is considered for PV array designed with an MPPT based on Perturb & Observe Algorithm. A fuel cell stack with constant Hydrogen and air is considered. Here, the non-conventional energy sources are connected to Conventional grid. The variable DC obtained after Solar array is converted to three phase A.C by means of a three-phase inverter. The pulses for the inverter are generated by taking voltage and current both from grid side and PV side respectively as reference. Here, the control strategy to produce pulses for inverter is based on Phase locked loop (PLL) with a PI controller. One of the most important power quality indices like Total Harmonic Distortion (THD) is measured at various points and the power quality is improved by using a Cascaded LC filter.Â